2003
DOI: 10.1097/00042737-200310000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic venous pressure gradient determination in patients with hepatitis C virus-related and alcoholic cirrhosis

Abstract: The degree of portal hypertension in cirrhotic patients does not correlate with the cause of the disease. Thus, current statements on the management of portal hypertension, although based upon studies including mainly patients with alcoholic cirrhosis, can be applied also to patients with viral-related cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 22 publications
1
16
0
3
Order By: Relevance
“…However, the difference in the etiology of cirrhosis in the three groups would not have altered our results. It has been previously shown that the degree of portal hypertension is not related to the etiology of cirrhosis [12,29], and we expect HVPG to be similar in different etiologies.…”
Section: Discussionmentioning
confidence: 66%
“…However, the difference in the etiology of cirrhosis in the three groups would not have altered our results. It has been previously shown that the degree of portal hypertension is not related to the etiology of cirrhosis [12,29], and we expect HVPG to be similar in different etiologies.…”
Section: Discussionmentioning
confidence: 66%
“…2) (expressed as difference between the last and first measurement) had a weak correlation with changes in fibrosis score (r ϭ 0.30, P ϭ 0.045). However, no significant correlation was found between change in grade and HVPG (P ϭ 0.042) and median HVPG did not change (5 mmHg; range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Regarding the whole paired group, the mean of the first evaluations for HVPG was 5.31 Ϯ 2.9 vs. 6.29 Ϯ 4.5 for the last (P ϭ 0.82); when evaluating those with PHT at first measurement, a better correlation was found, with mean first HVPG at 8.4 Ϯ 2.3 vs. 10 Ϯ 5 for the last HVPG (P ϭ 0.076).…”
Section: Total Cohortmentioning
confidence: 99%
“…10 Other studies have correlated HVPG both with severity and etiology of cirrhosis, 3,7,11 with only 1 study documenting a difference between HCV and alcoholic cirrhosis. 12 A significant correlation has been shown between antiviral response and HVPG changes in HCV chronic hepatitis, 13,14 and between HVPG and histological features of cirrhosis. 15 HVPG Ͼ10 mmHg predicts the development of complications of HCV cirrhosis.…”
mentioning
confidence: 99%
“…Measurement of the hepatic venous pressure gradient (HVPG) [the wedged hepatic venous pressure (WHVP) -the free hepatic venous pressure (FHVP)] is a simple, safe procedure and it accurately reflects the portal pressure in patients with alcoholic [13] as well as posthepatitic cirrhosis [13,14,20]. It is now well established that portal pressure must increase above a threshold value of 12 mm Hg for variceal bleeding to occur [2,3].…”
Section: Introductionmentioning
confidence: 99%